2023
DOI: 10.1002/alz.12975
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical MRI staging of frontotemporal dementia variants

Abstract: INTRODUCTIONThe three clinical variants of frontotemporal dementia (behavioral variant [bvFTD], semantic dementia, and progressive non‐fluent aphasia [PNFA]) are likely to develop over decades, from the preclinical stage to death.METHODSTo describe the long‐term chronological anatomical progression of FTD variants, we built lifespan brain charts of normal aging and FTD variants by combining 8022 quality‐controlled MRIs from multiple large‐scale data‐bases, including 107 bvFTD, 44 semantic dementia, and 38 PNFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…One significant contribution of our study lies in utilizing over 700 core volumes, all coregistered within the same standard space, to infer longitudinal profiles of untreated stroke progression, drawing inspiration from methodologies applied in other domains (15)(16)(17)(18). In contrast to previous efforts that employed linear fitting (32), which simplifies the complex biological processes at play, we employed smooth curve fitting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One significant contribution of our study lies in utilizing over 700 core volumes, all coregistered within the same standard space, to infer longitudinal profiles of untreated stroke progression, drawing inspiration from methodologies applied in other domains (15)(16)(17)(18). In contrast to previous efforts that employed linear fitting (32), which simplifies the complex biological processes at play, we employed smooth curve fitting.…”
Section: Discussionmentioning
confidence: 99%
“…Only few data reported two imaging sessions prior to recanalization (14). An alternative method would consist of inferring pseudo-longitudinal profiles from the concatenation of a large number of homogeneous cross-sectional data collected before recanalization akin to strategies used recently to map the typical evolution of brain volume across the lifespan (15, 16) or in neurodegenerative diseases (17, 18). Indeed, if we could objectively attribute stroke patients presenting the same clot location to a specific growth phenotype, then, we could reconstruct stereotypical growth curves from such homogeneous cluster of patients explored at different time points after the onset of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…To study brain volumetric trajectories of PSP-RS across the entire lifespan and to extrapolate the early stages of PSP-RS, we followed the strategy we have previously proposed for Alzheimer’s disease and FTD. 18 , 19 Our framework was based on the assumption that neurodegeneration is a continuous and progressive process along disease progression. Therefore, to constrain the volumetric trajectories over the entire lifespan, we built our PSP-RS models using control MRIs taken before the age of the youngest patient.…”
Section: Methodsmentioning
confidence: 99%
“…Thanks to this methodology and its validation using ‘truly’ longitudinal data, we have recently proposed the anatomical MRI staging of Alzheimer’s disease 18 and the three clinical variants of frontotemporal dementia (FTD). 19 Here, we describe the progressive pattern of neuroanatomical variations between PSP-RS and normal aging.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the peak atrophy in SD at baseline was in the TPOsup, extending to the left middle temporal and ITG, fusiform, AMYG, and anterior cingulate cortex; With disease progression, atrophy becomes more distributed to the middle and inferior frontal lobes, posterior temporal gyrus, and inferior parietal areas (Collins et al, 2017;Peet et al, 2021;Planche et al, 2023). Although it has been widely accepted that SD is associated with predominant atrophy of ATL, limited evidence is available regarding both the structural and functional network abnormalities, especially the changes with disease progression.…”
Section: Disrupted Organization Of Structural and Functional Network ...mentioning
confidence: 99%